Perfil social y perfil antropométrico en el atletismo peruano juvenil de élite - Bravo, Salim (2019)
The aim of this study was to determine the anthropometric profile (n=82): body shape, body composition and proportionality, and the social profile (n=71), socioeconomic status, of high level Peruvian junior athletes according to their level of performance (national and international level). It also establishes correspondences between athletics events, level of performance, the anthropometric profile and the social profile of these athletes. The results show that the sprinters and jumpers were predominantly mesomorphic. National long distance runners were mesoectomorphic. It was noted that while the performance level increases, the sprinters decrease their amount of body fat. In the jumpers, the fat mass and skin mass decrease while the competitive level increases. National long distance runners have a lower subcutaneous adiposity compared to the sprinters. Compared with other events (national sprinting, national jumping and national long distance running), the throwers are physically larger and heavier. Peruvian junior athletes mainly belong to the socioeconomic level A. In conclusion, the Peruvian junior athletes are divided or categorized morphologically and socioeconomically. Peruvian athletes that are close to the morphological and social characteristics of international and olympic athletes will be better chances to succeed at the high level.